Retire later or work harder? - David N.F. Bell; Robert A. Hart (Institute for the Study of Labor (IZA), 2010)
We compare two policies of increasing British state pension provision: (a) increase the pensionable age of men and women, (b) maintain the existing retirement age but require older workers to work longer per-period hours. There are reasons for policy makers to give serious consideration to the under-researched alternative (b). First, from wage - hours contract theory we know that there are potential gains to both workers and firms of allowing hours to rise in work experience. Second, there is strong evidence that job satisfaction rises in age. Third, there has in any case been a significant overall increase in the hours supplied by older workers in the last two decades. We review the relevant theory, model the trade-off between later retirement versus increased work intensity, produce relevant background facts, and provide estimates of the policy trade-offs.
Keywords: H55; J11; J14; J18; J22; J26; 330; Older workers; statutory retirement age; hours of work; Rentenfinanzierung; Altersgrenze; Ältere Arbeitskräfte; Arbeitszeitflexibilisierung; Arbeitsintensität; Rentenpolitik; Großbritannien